S134 How specific are fluorogenic substrates designed to analyse active protease biomarkers of respiratory disease?. (15th November 2016) - Robb, CM; Ferguson, TEG; Moffitt, KL; Downey, DG; McCafferty, DF; Ribeiro, D; Martin, SL; Walker, B
Abstract : Introduction: Active proteases, such as neutrophil elastase (NE) and matrix metalloproteinases (MMPs), have been established as inflammatory biomarkers in lung diseases such as cystic fibrosis (CF), chronic obstructive pulmonary disease (COPD) and pulmonary fibrosis. Therefore, biological samples collected during clinical investigations are often analysed using fluorogenic substrates to determine protease activity and identify correlations with clinical and/or demographic parameters. Due to the nature of these diseases, samples often contain numerous active proteases from both human and bacterial origins which collectively have significant substrate crossover. This study investigates the ability of fluorogenic substrates to distinguish between proteases in complex clinical samples and provide an indication of the predictive capability of this assay type. Methods: Expectorated sputum was randomly collected from patients with CF who were hospitalised for an acute exacerbation. Samples were processed within 30 minutes of collection, and the aqueous sol recovered, pooled, aliquoted and stored at −80°C until analysis. The capacity of sputum proteases to hydrolyse fluorogenic substrates with and without the presence of inhibitors specific for serine (multiple subclasses), metallo and cysteine proteases was examined. Fluorogenic substrates analysed include those for various inflammatory proteases including elastase-like (MeOSuc-AAPV-AMC), MMPs (MCA-PLGL-Dpa-AR-NH2), trypsin-like (Z-GGR-AMC) and chymotrypsin-like (Suc-AAPF-AMC). Substrate hydrolysis by a relevant recombinant enzyme (± inhibitors) was analysed as a control. Results: Data analysis indicates that alternative enzymes actively hydrolyse substrates designed to be specific for one group of proteases. Inhibitors specific for metallo, trypsin-like, chymotrypsin-like and cysteine proteases all decreased elastase-like substrate turnover (∼10–50%). A similar trend was seen for chymotrypsin-like substrate using metallo, trypsin-like and elastase-like protease inhibitors (∼10–40%). Conclusion: This investigation has suggested that there is significant non-specific hydrolysis and cross-reactivity when fluorogenic substrates are utilised to measure active proteases in complex biological samples. Thus, using such fluorogenic substrates may produce elevated readings, impacting on the accuracy of results when such assays are used for clinical or research purposes.